Public Perception of The Implementation of an Eco Fishig Port Priciple at The Fish Auction Place of Karangantu, Serang City - Wicaksono, Anggit Prabu; Susanto, Adi; Nurdin, Hery Sutrawan (Agrikan Jurnal Agribisnis Perikanan, 2023)
Eco port is a predicate of a port that has implemented systematic efforts or steps to build and maintain an environmentally friendly port area. Poor sanitation and hygiene conditions such as large amounts of waste from fishing port activities can cause environmental pollution and affect public health. This research aims to determine public perception towards the management of the Fish Landing Place (TPI) of Karangantu in accordance with the principle of eco fishing port. Primary data was obtained through observations in July-August 2022 on ship unloading activities until the transaction process at Karangantu TPI. Interviews with Karangantu Archipelagic Fishing Port (PPN) employees, TPI managers and TPI service users were conducted to find out each stakeholder's perception of environmental sanitation conditions and hygiene of fish catches. Secondary data were obtained from various publications available in Karangantu PPN. Data were analyzed descriptively qualitatively (tables and graphs) and quantitatively (Likert scale). The results showed that the management of Karangantu TPI is in accordance with the eco port principle. However, the public considers that the parameters of liquid waste handling and the quality of fish catches landed at TPI Karangantu must be improved.